2020
DOI: 10.18103/mra.v8i2.2039
|View full text |Cite
|
Sign up to set email alerts
|

NT-proBNP Level Predicts Extent of Myonecrosis and Clinical Adverse Outcomes in Patients with ST-Elevation Myocardial Infarction: A Pilot Study

Abstract: Background and Hypothesis: The initial assessment of late gadolinium enhancement (LGE) on cardiac magnetic resonance imaging (CMR) reflects cardiac damage and is an important prognostic factor in patients with acute ST-elevation myocardial infarction (STEMI). N-Terminal prohormone of brain natriuretic peptide (NT-proBNP) is released following cardiomyocytes injury. However, the relationship between NT-proBNP levels, myocardial damage and clinical outcomes after STEMI has not been well defined. Methods: Plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
(12 reference statements)
1
4
0
Order By: Relevance
“…Shavadia et al (19) have found that only one biomarker (higher pre-PCI NT-pro BNP levels) was connected to a congestive heart failure, notably higher 90-day risk of death, and cardiogenic shock. This also agrees with the findings of Qin et al (20) and Mathbout et al (22) who revealed that NT-pro BNP was a crucial predictor of MACE in cases with STEMI. These findings suggest that early risk stratification of cases at high risk for poor myocardial reperfusion including NT-pro BNP measurement is very important.…”
Section: Discussionsupporting
confidence: 93%
“…Shavadia et al (19) have found that only one biomarker (higher pre-PCI NT-pro BNP levels) was connected to a congestive heart failure, notably higher 90-day risk of death, and cardiogenic shock. This also agrees with the findings of Qin et al (20) and Mathbout et al (22) who revealed that NT-pro BNP was a crucial predictor of MACE in cases with STEMI. These findings suggest that early risk stratification of cases at high risk for poor myocardial reperfusion including NT-pro BNP measurement is very important.…”
Section: Discussionsupporting
confidence: 93%
“…The researchers found that the peak levels of CKMB and cTnT were significantly correlated with the infarct size and could predict mortality within 1 year 15 . The peak level of NT-proBNP was positively correlated with the severity of myocardial injury and the risk of adverse prognosis in patients with acute myocardial infarction 16 . In this study, by monitoring the peak levels of hs-cTnT, CKMB and NT-proBNP, we found that the higher the MIRI manifestation grade of STEMI patients, the higher was the biomarker level of myocardial injury and the lower was the grade of STEMI patients who also had myocardial injury.…”
Section: Discussionmentioning
confidence: 92%
“…The prognostic impact of NT-pro-BNP in STEMI patients has been anticipated in previous studies [23,24]. Mohammad et al [25] showed that the change in pNT-proBNP values following STEMI were predictive of the extent of myocardial damage and clinical outcomes. Sabatine MS et al [26] revealed the enhanced predictive and prognostic power of short-term risk stratification by exploiting the sST2 level change combined with the NT-proBNP level in STEMI patients.…”
Section: Discussionmentioning
confidence: 57%